LEGAL RESPONSIBILITIES AND PROTECTION OF PATIENT PRIVACY IN THE USE OF VIRTUAL REALITY AS A NEW METHOD IN DRUG ABUSE REHABILITATION - Jonly Harmon Hadi Purba; Henry Aspan; Muhammad Azhali Siregar (PT. Sinergi Legal Publisher, 2025)
Virtual Reality (VR) technology has been rapidly developing and applied in various fields, including medicine. In the context of drug abuse rehabilitation, VR offers an innovative therapeutic approach that is effective in reducing the desire to use drugs. In Indonesia, drug abuse continues to increase, especially among adolescents, so an effective rehabilitation method is needed. Although VR shows great potential, its application poses legal challenges, especially related to legal liability and protection of patient privacy. This study analyzes the existing legal framework in Indonesia and highlights the need for stricter regulations to ensure patient safety and privacy in the use of VR. A comprehensive legal approach will support the development of VR as a safe and ethical rehabilitation method.